COE Inhibits Vasculogenic Mimicry by Targeting EphA2 in Hepatocellular Carcinoma, a Research Based on Proteomics Analysis - Chu, Zewen; Shi, Xin; Chen, Gaoyang; He, Xuejun; Qian, Yayun; Wang, Haibo; Tao, Li; Liu, Yanqing; Jiang, Wei; Chen, Jue (Frontiers in Pharmacology, 2021)
New strategies and drugs are urgently needed to improve the treatment of hepatocellular carcinoma (HCC). Vasculogenic mimicry (VM) has been elucidated being associated with the progression of HCC and anti-VM could be a promising strategy. Celastrus orbiculatus extract (COE), a mixture of 11 terpenoids isolated from the Chinese Herb Celastrus Orbiculatus Vine, has been elucidated to be able to disrupt VM formation in HCC. This study aims to dissect and identify the potential targets of COE on anti-VM formation both in vitro and in vivo that are distinct from our previous study. Proteomics analysis was used to identify differential proteins in HCC cells treated with or without COE. Cells invasion was examined using Transwell. Matrigel was used to establish a 3-D culture condition for VM formation in vitro. RT-PCR and Western Blot were used to examine changes of mRNA and protein respectively. Clinical resected samples were applied to confirm association between VM formation and identified targets. Subcutaneous xenograft tumor model was established to observe tumor growth and VM formation in vivo. PAS-CD34 dual staining was used to detect VM in vivo. A total of 194 proteins were identified to be differentially expressed in HCC cells treated with or without COE. In the 93 down-regulated proteins EphA2 stood out to be regulated on both RNA and protein level. Disruption EphA2 using COE or NVP inhibited VM formation and decreased VM associated biomarkers. In xenograft mouse model, COE inhibited tumor growth and VM formation via down-regulating EphA2. Taken together, our results indicate that COE could be used in HCC treatment because of its promising anti-VM effect.